Genome Sequencing of up to 6, 000-Year-Old Citrullus Seeds Reveals Use of a Bitter-Fleshed Species Prior to Watermelon Domestication. (30th July 2022) - Pérez-Escobar, Oscar A; Tusso, Sergio; Przelomska, Natalia A S; Wu, Shan; Ryan, Philippa; Nesbitt, Mark; Silber, Martina V; Preick, Michaela; Fei, Zhangjun; Hofreiter, Michael; Chomicki, Guillaume; Renner, Susanne S
Abstract: Iconographic evidence from Egypt suggests that watermelon pulp was consumed there as a dessert by 4, 360 BP. Earlier archaeobotanical evidence comes from seeds from Neolithic settlements in Libya, but whether these were watermelons with sweet pulp or other forms is unknown. We generated genome sequences from 6, 000- and 3, 300-year-old seeds from Libya and Sudan, and from worldwide herbarium collections made between 1824 and 2019, and analyzed these data together with resequenced genomes from important germplasm collections for a total of 131 accessions. Phylogenomic and population-genomic analyses reveal that (1) much of the nuclear genome of both ancient seeds is traceable to West African seed-use "egusi-type" watermelon ( Citrullus mucosospermus ) rather than domesticated pulp-use watermelon ( Citrullus lanatus ssp. vulgaris ); (2) the 6, 000-year-old watermelon likely had bitter pulp and greenish-white flesh as today found in C. mucosospermus, given alleles in the bitterness regulators ClBT and in the red color marker LYCB ; and (3) both ancient genomes showed admixture from C. mucosospermus, C. lanatus ssp. cordophanus, C. lanatus ssp. vulgaris, and even South African Citrullus amarus, and evident introgression between the Libyan seed (UMB-6) and populations of C. lanatus . An unexpected new insight is that Citrullus appears to have initially been collected or cultivated for its seeds, not its flesh, consistent with seed damage patterns induced by human teeth in the oldest Libyan material.